Implementasi Etika Bisnis Islam Pelaku Usaha Mikro : Studi Kasus Pada Pelaku Usaha Mikro Syariah Puspa Bank Indonesia Wilayah Jawa Barat Di Bandung Tahun 2017 - Juliana, Juliana; Faathir, M.; Sulthan, M. A. (Universitas Pendidikan Indonesia, 2019)
This research is based on the phenomena of problems that exist in MSMEs including poor administration, low product competitiveness, low human resources, lack of mastery of science, quality of service and use of quality goods (Halal Thayyib). The purpose of this study was to measure the level of implementation of Islamic Business Ethics for MSME players in the PUSPA Bank Indonesia program in West Java in Bandung in 2017. The research method used was quantitative descriptive with data analysis techniques using descriptive statistics. The number of research samples is 50 consumers from 4 MSMEs engaged in the culinary, service, fashion and craft sectors. The results of the study show that the level of implementation of Islamic Business Ethics of micro business actors guided by the PUSPA program in Bank Indonesia in West Java in 2017 was very good. This can be seen from several dimensions used, namely honesty, the use of good quality goods, Ihsan, Building good relations with Consumers and Ethics sets the price of an average value of 5.8 which means very good